(untitled) (Journal of Engineering, 2009)
Several sophisticated or "optimum" modulation strategies have been suggested for voltage source pulse with modulated (PWM) inverters for ac motor control. These modulation strategies may suppress specific low – order harmonics or minimize total harmonic. The effectiveness of these (PWM) techniques in minimizing harmonic and reducing torque pulsation is investigated analytically, and their performance is compared with that of the usual sinusoidal or sub-harmonic PWM approach. The influence of skin effect on motor (I2R copper losses) is taken into consideration, and harmonic core losses are compared. Peak current is also an important factor in inverter design, and the various modulation strategies are again compared on this basis. Fourier analysis techniques are used in order to allow skin effect phenomena to be taken into consideration and performance criteria are developed to allow comparisons of waveform quality with respect of harmonic copper and iron losses.